1970
DOI: 10.1007/bf00189821
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hydrostatic pressure on the ductility of metals and alloys

Abstract: A law governing the change in the ductility of metals and alloys under pressure is given:where P is the hydrostatic pressure, elo¢,1 is the strain accumulated from the start of necking to fracture, f, necking stress and (df/ds) the coefficient of linear work hardening. This relation is derived from a newly proposed criterion of ductile fracture, viz. "constancy of hydrostatic tensile stress", which indicates that the change of ductility with pressure obeys a three halves power law. The observed increase in duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Since the magnitude of 2 will range between these two cases, the critical hydrostatic pressure will be limited by Equations ( 5) and (6). Since o and f are positive by definition, the critical hydrostatic pressure found by Equation (6) will always be algebraically smaller than the corresponding value found by Equation (5).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Since the magnitude of 2 will range between these two cases, the critical hydrostatic pressure will be limited by Equations ( 5) and (6). Since o and f are positive by definition, the critical hydrostatic pressure found by Equation (6) will always be algebraically smaller than the corresponding value found by Equation (5).…”
Section: Discussionmentioning
confidence: 96%
“…From the literature, it has been shown that hydrostatic pressure is a parameter which has great influence on the initiation and propagation of damage in materials [2][3][4][5][6][7]. This has been documented for metal forming processes [19,23] and for MMCs tested in tension with superimposed hydrostatic pressures [8][9][10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it can be seen, the scale of the pin deformation is significantly higher than what is possible in the monotonic tension test. The scale of this deformation is likened to the presence of high hydrostatic pressures (typically 1.5 GPa) under the point of contact which is known to make brittle materials more ductile [30,31].…”
Section: Strain Analysismentioning
confidence: 99%
“…The reason behind this seemingly ductile response of a brittle metal can be explained by the presence of high hydrostatic pressures. It has been shown that brittle metals behave as ductile metals when subjected to hydrostatic pressure [22,23], and it is typical under rough surface contact for high stresses generated under the point of contact to cause high hydrostatic pressures in the subsurface [18]. Therefore, one cannot assume the material will necessarily behave in a brittle manner during wear in the presence of these pressures.…”
Section: Wear Testsmentioning
confidence: 99%